Question
Asked Oct 12, 2019

-18 + 4(6 ÷ 2)2

check_circle

Expert Answer

Step 1

Given:

The expression is -18+4(6 2)
help_outline

Image Transcriptionclose

The expression is -18+4(6 2)

fullscreen
Step 2

Simplify the expressi...

Solvebrackets first by dividing the number 6 by 2.
18 4(6 2)-18+ 4(3)
Multiply 4, 3 and 3
-18+4(6 2)18+4(3)
=-18 +36
Now subtract 18 from 36.
-18 4(6 2)-18+4(3)
=-18 +36
=36 -18
=18
help_outline

Image Transcriptionclose

Solvebrackets first by dividing the number 6 by 2. 18 4(6 2)-18+ 4(3) Multiply 4, 3 and 3 -18+4(6 2)18+4(3) =-18 +36 Now subtract 18 from 36. -18 4(6 2)-18+4(3) =-18 +36 =36 -18 =18

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Algebra